Agreement of patient-measured intraocular pressure using rebound tonometry with Goldmann applanation tonometry (GAT) in glaucoma patients - Shaoying Tan (2018)
This study aims to determine the agreement of patient-Measured intraocular pressure (IOP) using rebound tonometry with ophthalmologist-measured IOP using Goldmann applanation tonometry (GAT). Fifty-three glaucoma patients used rebound tonometry (Icare ONE, Icare Finland Oy., Finland) to measure their own IOP in ambient environments for 1 week, 5 times per day. Clinic IOP measurements were performed by ophthalmologists using GAT and by patients using rebound tonometry on examination days 1, 4 and 7 of the same week. The agreement between the two tonometries was evaluated by modified Bland-Altman plots and intra-class correlation coefficient (ICC) was determined. Differences in ICCs of them among the three examination days were evaluated by bootstrap resampling analysis. Respective within-measurement ICC of GAT and rebound tonometry were 0.98 and 0.94 on Day 1, 0.98 and 0.93 on Day 4, and 0.96 and 0.92 on Day 7. In a modified Bland-Altman plot, the mean difference ±1 standard deviation (SD) between the two tonometries was 0.15 ± 0.65 mmHg (p = 0.682). Between-Measurement ICC were 0.66, 0.76 and 0.73 on the 3 examination days. There was no significant difference among ICCs. In conclusion, patient-Measured IOP using rebound tonometry and ophthalmologist-Measured IOP using GAT demonstrate good agreement.